2017
DOI: 10.3389/fmicb.2017.00651
|View full text |Cite
|
Sign up to set email alerts
|

Japanese Encephalitis Virus Exploits Dopamine D2 Receptor-phospholipase C to Target Dopaminergic Human Neuronal Cells

Abstract: Despite the availability of vaccines for Japanese encephalitis virus (JEV), the re-emerging virus remains a clinically important pathogen that causes acute encephalitis and permanent neuropsychiatric sequels. JEV highly targets dopaminergic neuron-rich brain regions including the thalamus and midbrain. The molecular mechanism contributing to the high susceptibility of these particular brain regions remains largely unclear. This study addressed whether this tissue tropism of JEV is associated with signaling of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 42 publications
(57 reference statements)
1
59
0
Order By: Relevance
“…JEV can enter human neuronal cells by caveolin-mediated endocytosis ( 115 ), a process that is receptor-independent ( 116 ). Interestingly, JEV has been shown to utilize the dopaminergic signal transduction pathway to increase neuronal susceptibility to infection ( 117 ). Infection of human dopaminergic neuroblastoma cells in vitro leads to increased levels of secreted dopamine and activation of the phospholipase C cascade.…”
Section: Japanese Encephalitis Virusmentioning
confidence: 99%
“…JEV can enter human neuronal cells by caveolin-mediated endocytosis ( 115 ), a process that is receptor-independent ( 116 ). Interestingly, JEV has been shown to utilize the dopaminergic signal transduction pathway to increase neuronal susceptibility to infection ( 117 ). Infection of human dopaminergic neuroblastoma cells in vitro leads to increased levels of secreted dopamine and activation of the phospholipase C cascade.…”
Section: Japanese Encephalitis Virusmentioning
confidence: 99%
“…The current study showed that the effect of AT1R on the behavioral effects of METH was associated with the changes in CREB and PLCb, along with the altered activity of D2R. There has been growing evidence about the interaction between D2R and Reduced inositol monophosphate level, which indicated lower activity of PLC, was evident in cells with D2R knockdown (Simanjuntak et al, 2017). Motor skill learning deficits induced by the D2R antagonist raclopride were prevented by the coadministration of the PLC agonist m-3m3fbs (Rioult-Pedotti et al, 2015).…”
Section: Discussionmentioning
confidence: 57%
“… 2 19 In study of patients suffering for MERS, neurological manifestation was also reported in few patients. 20 21 So, it is quite imperative to presume that the current pandemic will also have patients presenting with different neurological manifestations. Some of these manifestations will be specifics such as cerebrovascular accidents, seizures, meningitis, and encephalitis, whereas majority will have nonspecific symptoms such as confusion, dizziness, headache, and myalgia.…”
Section: Discussionmentioning
confidence: 99%